Oral Health Status and Oral Health-Related Behaviors of Patients Visiting Tertiary Care Hospital in Quetta, Pakistan - Khan M.A. (2023)
Objective: To determine the oral health status and oral health practices among patients visiting a tertiary care hospital in Quetta, Pakistan. Study Design: Cross-Sectional Study Place and Duration of Study: This study was conducted at Sandeman Provincial Civil hospital Quetta, Pakistan in March 2021. Materials and Methods: The target population of this study was patients aged 18 to 65 years visiting the dental OPD of the hospital. Four hundred patients, including 210 males and 190 females, participated in the study. According to WHO oral health survey methods (5th edition). The face-to-face interview was carried out to examine the socio-demographic factors, attitude, behavior, and oral health practices of the patients. Descriptive statistics were reported for participants’ characteristics, oral health practice, and oral health status. Logistic regression was performed to analyze the association of multiple variables with a significance level of 0.05. Results: Results of this study revealed that 77.0% of the participants had high DMFT scores (DMFT>5), 95.5% had gingival bleeding, 52.5% had periodontal pocket (4-5mm or above), 85.5% had poor/fair oral hygiene, and 16.5% had some kind of oral lesions. Socio-economic factors, tooth brushing frequency, use of toothbrushes and toothpaste, dental visits, and tobacco use were significantly associated with patients’ poor oral health status, including dental caries and periodontal diseases. Conclusion: After adjusting for age and education, low tooth brushing frequency, no use of toothbrush and toothpaste, less frequent dental visits, and tobacco use were the contributing factors for the poor oral health status of the participants.